Utilization of Tiwai Onion Nanoparticles (Eleutherine amaricana Merr) as Feed Mixture Towards Quality of Broiler Carcass - Manullang, Julinda Romauli; Parinding, Gidion (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2023)
This study aims to determine the best concentration of Tiwai Onion nanoparticles and the effect of giving Tiwai Onion nanoparticles on the quality of meat and organoleptic broilers. Method: This study used a Completely Randomized Design (CRD) with five treatments and five repetitions, each repeat consisting of five broilers, using 125 broilers raised for 35 days. The research parameters were carcass weight, carcass protein, abdominal fat, carcass fat, and organoleptic tests.P0 represented the control or no administration of Tiwai Onion nanoparticles, whereas P1 0.2%, P2 0.4%, P3 0.6%, and P4 0.8% administration of Tiwai onions. The data obtained on carcass weight, abdominal fat, and organoleptic were then analyzed using One Way Anova and Duncan's test, while carcass protein and carcass fat were analyzed descriptively. The results showed that the administration of Tiwai Onion nanoparticles had no significant (P>0.05) influence on the percentage of carcass weight, texture, and scent of broiler chickens, but had a significant (P0.05) effect on the percentage of abdominal fat and meat colour Conclusion: This indicates that the addition of the highest level tiwai Onion nanoparticles resulted in positive carcass protein and fat values.